Compositional artifice in the music of Henry Purcell - Howard, Alan 1979- (Cambridge University Press, 2020)
Fugal invention has proved a successful line of analytical inquiry in recent studies of repertoires from Josquin to J. S. Bach. Alan Howard brings similar insights to the music of Henry Purcell, and proposes the first analytical approach to his music to examine compositional methods alongside historically contemporary theory, focusing particularly on Purcell's 'artificial' approach to imitative counterpoint. Through this methodology Howard challenges many misunderstandings about Purcell's music that led to him being categorized as old-fashioned and unimaginative. This study offers fresh insights into the musical world in which Purcell lived and worked and situates Purcell's compositional concerns in the broader context of notions of artifice in Restoration culture. Howard thereby offers both a fresh analytical approach - both to Purcell's early instrumental works and to his later concerted vocal music - and a critique of the reception history surrounding the fantazias and sonatas in particular
Keywords: Purcell, Henry -- 1659-1695; Geschichte; Komposition -- Musik; Purcell, Henry / 1659-1695 / Criticism and interpretation; Music / 17th century / Analysis, appreciaton; Composition (Music) / History / 17th century; Purcell, Henry / 1659-1695; Composition (Music); 1600-1699; Criticism, interpretation, etc; History; Hochschulschrift